Invisible Scars or Open Wounds? The Role of Mid-career Income for the Gender Pension Gap in Sweden - König, Stefanie; Johansson, Boo E. A.; Bolin, Kristian (Frontiers in Sociology, 2019)
This study investigates the importance of mid-career income for the gender pension gap and psychological scarring effects of low income earlier in life. More specifically we analyse whether women’s typically less stable mid-life careers also affect outcomes in late careers and in retirement. Swedish income register data from 1990, 2009 and 2015 was linked to the ‘Health, Ageing and Retirement Transitions in Sweden” survey. The gender pension gap of 966 retirees and worries about pension income of 2723 older workers between the age of 60 and 66 years were investigated. Blinder-Oaxaca decompositions were applied to analyse the gender pension gap and linear regressions were used for the analysis of financial worries. Results show that gender differences in mid-career income play a stronger role for the gender pension gap than late career income. Mid-career income is furthermore related to higher worries about pension income and accounts for observed gender differences. Our findings demonstrate that gender gaps in mid-career income can be regarded as an open wound with visible negative effects in older ages. The reformed pension system in Sweden may potentially contribute to an even greater gender gap in pensions.